PENERAPAN STRATEGI PEMBELAJARAN AKTIF PLANTED QUESTIONS UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KOLOID DI KELAS XI MIA SMA NEGERI 12 PEKANBARU - Sari Ayu Sabatini; Herdini '; Erviyenni ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The aim of this research is to improve the students learning achievement on the subject colloids with implementation Planted Questions active strategies. Kind of research was an experiment research with randomized control pretest-posttest group design. Retrieval of data starting from May - June 2015 in SMAN 12 Pekanbaru. Samples of research are class XI science 3 as the experiment class (applied Planted Questions active strategies) and class XI science 4 as the control class (with ordinary learning) were randomly selected after normality test and homogeneity test. Data collection method used is the testing techniques. The analysis techniques consist of 3 techniques that are normality test was used Liliefors test to verify data is normally distributed, homogeneity test was used variance test and t-test to see same ability learning of samples, and hypothesis test was used t-test to validate the hypothesis. Based on the hypothesis test obtained tcount> ttable is 2,561 > 1,668. The meaning that the implementation of Planted Questions active strategies can improve students achievement on the subject of colloids in class XI science SMAN 12 Pekanbaru. The improvement of students learning achievement in the experiment class was supported by the influence coefficient value of 8,57%.Keywords: Colloid, Active Strategies, Learning Achievement, Planted Questions.